Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V SDN 64 Galunggung - Sintian Tombalisa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Basic education is crucial for a child's development before entering higher education. Children with a solid basic education will have a much easier time navigating higher education in the future. Mathematics is a subject and an important basic science, both as an aid, as a guide for thought patterns, and as a shaper of attitudes. Therefore, mathematics is expected to be mastered by students in school. However, mathematics is often considered difficult and feared by students, resulting in less active learning, which significantly impacts student achievement. This study aims to improve the learning outcomes of fifth-grade students at SDN 64 Galunggung by applying the inquiry model to fraction and division operations. This study uses a quantitative research type that aims to examine how the application of the inquiry model can improve students' mathematics learning outcomes. The study was conducted at SDN 64 Galunggung Elementary School. The research sample was all fifth-grade students and the homeroom teacher.